Bleeding and thrombotic risk in pregnant women with Fontan physiology. Issue 17 (24th November 2020) - Girnius, Andrea; Zentner, Dominica; Valente, Anne Marie; Pieper, Petronella G; Economy, Katherine E; Ladouceur, Magalie; Roos-Hesselink, Jolien W; Warshak, Carri; Partington, Sara L; Gao, Zhiqian; Ollberding, Nicholas; Faust, Michelle; et al.
Abstract : Background/objectives: Pregnancy may potentiate the inherent hypercoagulability of the Fontan circulation, thereby amplifying adverse events. This study sought to evaluate thrombosis and bleeding risk in pregnant women with a Fontan. Methods: We performed a retrospective observational cohort study across 13 international centres and recorded data on thrombotic and bleeding events, antithrombotic therapies and pre-pregnancy thrombotic risk factors. Results: We analysed 84 women with Fontan physiology undergoing 108 pregnancies, average gestation 33±5 weeks. The most common antithrombotic therapy in pregnancy was aspirin (ASA, 47 pregnancies (43.5%)). Heparin (unfractionated (UFH) or low molecular weight (LMWH)) was prescribed in 32 pregnancies (30%) and vitamin K antagonist (VKA) in 10 pregnancies (9%). Three pregnancies were complicated by thrombotic events (2.8%). Thirty-eight pregnancies (35%) were complicated by bleeding, of which 5 (13%) were severe. Most bleeds were obstetric, occurring antepartum (45%) and postpartum (42%). The use of therapeutic heparin (OR 15.6, 95% CI 1.88 to 129, p=0.006), VKA (OR 11.7, 95% CI 1.06 to 130, p=0.032) or any combination of anticoagulation medication (OR 13.0, 95% CI 1.13 to 150, p=0.032) were significantly associated with bleeding events, while ASA (OR 5.41, 95% CI 0.73 to 40.4, p=0.067) and prophylactic heparin were not (OR 4.68, 95% CI 0.488 to 44.9, p=0.096). Conclusions: Current antithrombotic strategies appear effective at attenuating thrombotic risk in pregnant women with a Fontan. However, this comes with high (>30%) bleeding risk, of which 13% are life threatening. Achieving haemostatic balance is challenging in pregnant women with a Fontan, necessitating individualised risk-adjusted counselling and therapeutic approaches that are monitored during the course of pregnancy.